2017
DOI: 10.1039/c7nj01373f
|View full text |Cite
|
Sign up to set email alerts
|

Facile and green one pot synthesis of zinc sulphide quantum dots employing zinc-based ionic liquids and their photocatalytic activity

Abstract: Zinc-based ionic liquids are found to be suitable candidates for the preparation of ZnS QDs, whose properties depend upon the alkyl chain length of imidazolium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 74 publications
0
11
0
2
Order By: Relevance
“…Magnetically separable nature of NPs renders the recycling process during different catalytic cycles very easy without the loss of NPs which resulted in negligible loss of catalytic efficiency over repeated number of catalytic cycles. The present report along with the earlier reported work on preparation of nanomaterials using ILs via hand grinding, 34,66,67 represents a simple, greener and economical method for the synthesis of a-Fe 2 O 3 NPs which show MIL dependent characteristics physicochemical properties of NPs and provides alternate way to manipulate the properties at nano level.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Magnetically separable nature of NPs renders the recycling process during different catalytic cycles very easy without the loss of NPs which resulted in negligible loss of catalytic efficiency over repeated number of catalytic cycles. The present report along with the earlier reported work on preparation of nanomaterials using ILs via hand grinding, 34,66,67 represents a simple, greener and economical method for the synthesis of a-Fe 2 O 3 NPs which show MIL dependent characteristics physicochemical properties of NPs and provides alternate way to manipulate the properties at nano level.…”
Section: Discussionmentioning
confidence: 77%
“…It is important to mention that the photodegradation of RhB, as a representative, using a-Fe 2 O 3 NPs can be scaled up for large scale industrial applications, where the use of sunlight would not only be cost-effective but also renders the process as a sustainable one. In this way, the present work along with the earlier reports on sustainable methods of preparation and catalytic applications of NPs 33,66 would pave the way for preparation and applications of new nanomaterials using MILs in an environment friendly manner.…”
Section: Photocatalytic Activity Of Synthesized A-fe 2 O 3 Npsmentioning
confidence: 70%
“…ZnS quantum dots were prepared using the Zn‐containing IL [C n MIm][ZnCl 3 ] ( n =4, 8, and 16) as a precursor, template, and solvent. [54] FeS 2 microspheres wrapped by N‐doped reduced graphene oxide were synthesized from the Fe‐based IL [C 12 MMIm][ FeCl 4 ]. [55] The Fe‐IL can be used as the metal and nitrogen source, an assembly medium, and surfactant.…”
Section: Reactions Of Metal‐containing Ionic Liquidsmentioning
confidence: 99%
“…The successful utilization of ionic liquids (ILs) in the syntheses of MCs, nanocarbons, and MCs/graphene composites sheds a light on resolving this issue. It has been shown that the ILs are good solvents and stabilizers for small‐sized MCs .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the ILs are good solvents and stabilizers for small‐sized MCs . In particular, the task‐specific metal‐containing ionic liquids (MILs) can function as “all‐in‐one” solvent/reactant/templates in synthesizing MCs nanomaterials, and MCs/graphene composites, which impose an important influence on the morphologies of the final composites and meanwhile simplify the reaction procedure.…”
Section: Introductionmentioning
confidence: 99%